The method of construction in the polemic dialogues of the unbelievers in the Holy Qur’an - a stylistic study (Journal of the College of Basic Education, 2022)
One of the things that draws the attention of the researcher is how to employ the declarative and constructional methods and their formations within the text, and how the dialogue moves from one style to another. Question: The question, the appeal, and the command. We have monitored the dialogues that included these methods and analyzed them according to the stylistic approach. It is an accurate approach in dealing with the text. It is one of the modern critical approaches that depend on analysis and interpretation in its dealings with the studied text, and it is a science that seeks to reveal On the characteristics and features of style that he distinguished by analyzing the text and observing the stylistic phenomena that distinguished it from other texts.